Almost like being there; the power of personas when designing for foreign cultures. Issue 4 (1st October 2016) - Vestergaard, Lise; Hauge, Bettina; Hansen, Claus Thorp
Abstract: Much research on personas focuses on how to develop and use personas, less on the validation and concrete value of them in the development of products for cultures far away from the actual design site. This article illustrates how such a validation was accomplished through producing a film and it provides an in-depth case description of how personas were developed and used. When designing a waste management system for soft plastic for a small village in India, personas were developed and applied by the designer to maintain a user-oriented focus throughout the participatory design process. During a three-month stay in the village, personas based on real people and the villagers' everyday life and practices were developed by getting to know people and their ways of life through the use of ethnographic methods (observations, interviews, workshops and a film). The personas created a substantial understanding of the users' individual needs, interests, values and emotions and helped to overcome the physical and cultural distance, enabling a strongly contextualised design.